Hortiterapia czy praca w ogrodzie – podobieństwa i różnice - Gulczyńska, Anna (Studia Edukacyjne, 2020)
There is growing attention to findand popularize untypical forms of therapy which should help patients in hospitals, occupational facilities and clinics. The main aim of the article is to show the differences between horticultural therapy as a form of therapy and work in a garden, which can also provide therapeutic results. Comparison of different determinants was a method to outline that proper understanding of the differences may be beneficialboth for theoreticians and practitioners who use nature in order to improve their patients’ health. However, it is useful for future teachers and could play a role in the teacher education process. As a conclusion, it has been established that source literature scientificreports focus rather on potential recipients or benefitswhich come from this form of therapy, whereas basic differences between gardening and horticultural therapy have been rarely mentioned. Analysis has helped to observe that there are many factors which differentiate therapeutic work in the garden from work in the garden which can bring therapeutic effects. Performing such an analysis seems to be significantin connection with the growing popularity of centers which offer this kind of therapy, and with the emergent dilemmas concerning how it differs from gardening and whether the therapy is worth the money invested in it.